A method for measuring droplet evaporation in a shock-driven multiphase instability. (December 2020) - Duke-Walker, Vasco; Allen, Roy; Maxon, W. Curtis; McFarland, Jacob A.
Highlights: A new method for measuring evaporation rates in a shock-driven multiphase instability is presented. Velocity and evaporation measurements are presented for a shock-driven multiphase instability for the first time. Evaporation rate is shown to be limited by large scale mixing between the saturated carrier gas and the surrounding dry gas. Graphical abstract: Abstract: Experimental measurements of bulk droplet evaporation within a shock-driven multiphase instability, or SDMI, were studied using advanced imaging diagnostics. Specifically, droplet evaporation was quantified by determining the rate of acetone vapor produced from liquid acetone droplets. The extent of the acetone vapor produced was measured using quantitative planar laser-induced fluorescence (Q-PLIF). In addition to vapor concentration, Q-PLIF also accounts for the effects of pressure and temperature on the fluoresced acetone. Concurrently performed with Q-PLIF were particle image velocimetry (PIV) measurements as the means to gather data on the acetone droplet's velocities as well as the particle fields morphology throughout its development. By using these two diagnostic techniques, two successive data points of the acetone droplets evaporation rate throughout the development of the SDMI were obtained. Although these first two data sets were not adequate to fully prescribe an accurate evaporation rate model, they were a sufficient corrigendum to the commonly-utilized D-squared evaporation law. Overall, the previous techniques have been demonstrated that acetone droplet evaporation can be measured quantitatively, enabling prediction of evaporation enhancement due to the strong hydrodynamic mixing within the SDMI.